Dietary Supplementation of Increasing Levels of DLMethionine and L-Lysine in Hypoproteic Diets for Laying Hens Improves Productivity and Egg Quality (2015)
To evaluate the effect of dietary supplementation of DL-methionine and L-lysine in hypoprotein diets on productivity and egg quality, a total of 240 White Leghorn laying hens (Hybrid L-33) of 26 weeks during laying peak period were placed for 49 days, according to completely randomized design with four treatments and 10 repetitions. Dietary treatments consisted of a control diet (no amino acid supplementation) (T0) and supplementation of 0.03% DL-Met and 0.04% L-Lys (T1), 0.06% DL-Met and 0.08% L-Lys (T2) and 0.09% DL-Met and 0.12% L-Lys (T3). At 26 and 33 weeks of age, 30 eggs per treatment were collected to determine internal and external egg quality parameters.The experiment diets did not affect the viability and feed intake. Supplementation of essential amino acids, especially the T3 improved egg weight (54.30 to 58.30 g), laying rate (76.89 to 85.45%) and mass conversion (2.52 to 2.11 kg/kg) (P&lt,0.05). At 33 week, the albumin height (7.21 to 8.23 mm), Haugh units (86.70 to 91.15) (P&lt,0.05) and shell surface (67.10 to 69.20 cm2) increased by the effect of supplementation of DL-Met and L-Lys. The results allow recommending the dietary supplementation of 0.09% DL-Met and 0.12% L-Lys in hypoprotein diets to improve productivity and egg quality in laying hens.